선체 용접부의 균열진전 및 피로수명예측에 관한 연구(Ⅱ) - 김경수(Kyung-su Kim); 심천식(Chun-sik Shim); 권영빈(Young-bin Kwon); 고희승(Hee-seung Ko); 기혁근(Hyeok-geun Ki); K.K. Viswanathan (大韓造船學會 論文集, 2008)
The fatigue life of ship structure under cyclic loading condition is made up of crack initiation and propagation stages. For a welding member in ship structure, the fatigue crack propagation life is more important than the fatigue crack initiation life. To calculate precisely the fatigue crack propagation life at the critical welding location, the knowledge of the residual stress sensitivity on the fatigue strength is necessary. In this study, thermo elastic-plastic analysis was conducted in order to examine the effect of residual stress on the fatigue crack propagation life. Also the fatigue crack propagation lives considering residual stress were calculated using fatigue crack growth code, AFGROW, on the basis of fracture mechanics. AFGROW is widely used for fatigue crack growth predictions under constant and variable amplitude loading. The reliability of AFGROW on the fatigue of ship structure was confirmed by the comparison of the estimated results with the fatigue propagation test results.